PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PEMBERDAYAAN MASYARAKAT DAN DESA PROVINSI MALUKU - Rafi, Rafif; Rengifurwarin, Zainal Abidin; Bahasoan, Aminah (JURNAL DARMA AGUNG, 2025)
This study examines the impact of employee competence on the performance of staff at the Office of Community Empowerment and Village Affairs in Maluku Province. Competence, which includes the knowledge, skills, and abilities of employees, plays a critical role in influencing their job performance. The research uses a quantitative approach with surveys conducted among employees of the office to gather data. The findings indicate a significant positive relationship between employee competence and their performance. Higher levels of competence, particularly in technical skills, leadership, and communication, are associated with improved job performance. This research also highlights the importance of continuous professional development and training to enhance employee competencies, which in turn can boost the overall performance of the office. The results suggest that improving the competence of government employees is a crucial factor in achieving better public service delivery, especially in the context of community empowerment and village development programs in Maluku. The study concludes that efforts to improve employee competence should be prioritized to ensure optimal organizational performance.